Hemin–G-quadruplex-crosslinked poly-N-isopropylacrylamide hydrogel: a catalytic matrix for the deposition of conductive polyaniline. Issue 11 (27th August 2015) - Lu, Chun-Hua; Guo, Weiwei; Qi, Xiu-Juan; Neubauer, Avner; Paltiel, Yossi; Willner, Itamar
Abstract : Conducting polyaniline is deposited into a G-quadruplex-crosslinked pNIPAM copolymer undergoing switchable stimuli-responsive solution/hydrogel/solid transitions. Abstract : A G-rich nucleic acid-tethered acrylamide/ N -isopropylacrylamide (NIPAM) copolymer is prepared. The nucleic acid-modified pNIPAM chains assemble, in the presence of K + ions, into a stimuli-responsive G-quadruplex-crosslinked pNIPAM hydrogel undergoing cyclic and reversible solution/hydrogel/solid transitions. Addition of kryptofix [2.2.2], CP, to the K + -stabilized G-quadruplex-crosslinked hydrogel eliminates the K + ions from the crosslinking units, resulting in the transition of the hydrogel into a pNIPAM solution. In turn, heating the pNIPAM hydrogel from 25 °C to 40 °C results in the transition of the hydrogel to the solid state, and cooling the solid to 25 °C restores the hydrogel state. Incorporation of hemin into the G-quadruplex-crosslinked hydrogel results in a catalytic hydrogel that catalyzes the oxidation of aniline by H2 O2 to form polyaniline. The polyaniline/pNIPAM hydrogel hybrid doped with 2 M HCl forms an emeraldine salt, which exhibits an electrical conductivity of 9 × 10 −4 [cm Ω] −1 .